2009
DOI: 10.1121/1.3132526
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental frequency influences the relationship between sound pressure level and spectral balance in female classically trained singers

Abstract: The influence of fundamental frequency (F0) on the relationship between sound pressure level (SPL) and spectral balance (SB) has been largely unexplored in the female singing voice. Five classically trained females performed a messa di voce across their musical F0 range. Average maximum SB rose with F0 by 0.27 dB/semitone (ST) to B4 and then decreased, while average minimum SB fell by 0.5 dB/ST to E5 and then generally rose. Of 318 tokens, 208 showed a linear SPL:SB relationship (R(2)>or=0.5), but F0 affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
(32 reference statements)
2
5
0
Order By: Relevance
“…et al. 16,26 All the SB maps confirm the often-reported trend 16 , 24 , 26 that, on average, the energy in the high end of the spectrum increases faster than does the SPL, which leads to progressively higher SB values with a higher SPL. As there are large intra-individual differences, it is questionable if Figure 8 represents a valid generalization.…”
Section: E14supporting
confidence: 69%
See 1 more Smart Citation
“…et al. 16,26 All the SB maps confirm the often-reported trend 16 , 24 , 26 that, on average, the energy in the high end of the spectrum increases faster than does the SPL, which leads to progressively higher SB values with a higher SPL. As there are large intra-individual differences, it is questionable if Figure 8 represents a valid generalization.…”
Section: E14supporting
confidence: 69%
“…In this vowel configuration, the low band generally carries the SPL and becomes synonymous with SPL. This pattern is rarely broken 16 ; and never with the participants in this study.…”
Section: Topic 3: Energy At High Frequencies Spectrum Balance Sbmentioning
confidence: 55%
“…Descriptive characteristics of patients referred for SVT revealed that most patients had a history of vocal training, sang nonclassical music, and were not professional singers. Much literature to date has focused on the contrary profile, professional classical singers . Although classical singers are certainly susceptible to voice disorders, vocal demands of nonclassical music may predispose patients to more vocal injury, leading to a greater number of nonclassical music singers referred to SVT.…”
Section: Discussionmentioning
confidence: 99%
“…Much literature to date has focused on the contrary profile, professional classical singers. 18,[31][32][33] Although classical singers are certainly susceptible to voice disorders, vocal demands of nonclassical music may predispose patients to more vocal injury, leading to a greater number of nonclassical music singers referred to SVT. It is known that at least one area of nonclassical music, musical theater, demands a heavy vocal load; many musical theater performers are expected to perform in eight shows per week.…”
Section: Discussionmentioning
confidence: 99%
“…First, we separated the total frequency range into two bands following the procedure used in several studies of trained singers. 6,31,49,50 However, we adapted the frequency range according to the participants' gender, considering that the female formant pattern is scaled upward about 20% compared with the average male formant pattern. The two bands were 0-2 kHz and 2-4.5 kHz for the male participants and 0-2.4 kHz and 2.4-5.4 kHz for the female ones.…”
Section: Acoustical Analysismentioning
confidence: 99%